The Role of Transparency in Mediating the Effects of Human Capital and E-Budgeting on Village Fund Accountability in Dompu Regency - Nawadiah Ramechi; Mulyati; firmansyah (Yayasan Sinergi Kawula Muda, 2026)
This study addresses the limited and inconsistent empirical evidence on the roles of human capital and digital financial systems in improving accountability in village fund management in Dompu Regency, West Nusa Tenggara, Indonesia, a setting underrepresented in public sector accountability research. While prior studies have examined these factors separately, insufficient attention has been given to how transparency functions as a mediating mechanism, a gap that limits both theoretical understanding and practical guidance on whether accountability improvements should target internal capacity and system adoption directly or through strengthening transparency as an intermediary mechanism. Drawing on stewardship theory and institutional theory, transparency is theorized as a mediator because it serves as the critical bridge through which improvements in internal capacity and system utilization become visible and verifiable to stakeholders without adequate transparency, gains in human capital and e-budgeting may not translate into accountable practices. This study therefore examines the effects of human capital and e-budgeting on accountability, with transparency positioned as a mediating variable. A quantitative approach was employed using purposive sampling of village government officials, with data collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings are predominantly nonsignificant across the proposed relationships, with the sole exception being the positive effect of human capital on e-budgeting. These results challenge the assumption that technical capacity and system adoption automatically generate accountability, suggesting that broader institutional and governance factors may play a more critical role though these implications should be interpreted with caution given the limited explanatory power of the model and the narrow geographic scope of this study.